2022
DOI: 10.1002/pchj.516
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and factors associated with mental health problems in Saudi general population during the coronavirus disease 2019 pandemic: A systematic review and meta‐analysis

Abstract: This systematic review and meta-analysis generates evidence of the prevalence and associated factors of common mental disorders (i.e., depression, anxiety, and stress) related to the pandemic among the Saudi general population. Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines, a comprehensive literature search was performed in the respective databases (e.g., PubMed, Scopus, Web of Science), from 22 July to 17 August 2021, and identified a total of 220 articles. Adheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
38
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
5
38
1
Order By: Relevance
“…Aligning with findings from a previous study among food truck customers in the city of Curitiba, Brazil [ 32 ], the present study reported that more than half of the consumers of food from FTs were female. Unfortunately, this observation in line with the street food segment is considered not typical of the female sex.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Aligning with findings from a previous study among food truck customers in the city of Curitiba, Brazil [ 32 ], the present study reported that more than half of the consumers of food from FTs were female. Unfortunately, this observation in line with the street food segment is considered not typical of the female sex.…”
Section: Discussionsupporting
confidence: 89%
“…Unfortunately, this observation in line with the street food segment is considered not typical of the female sex. The FTs promote eating as a cultural activity of leisure and fun that would be more attractive to males than females [ 32 ]. Studies that have reported more males than females as FTs consumers have indeed supported this justification [ 2 , 33 ], although on the contrary, globalization and women emancipation could be a better explanation for this study’s sex finding.…”
Section: Discussionmentioning
confidence: 99%
“…This observation indicates a trusted level of professionalism that is reassuring both to the medical profession in Saudi Arabia and patients. These results are also consistent with those of local and regional studies [21]. However, as noted in the introduction of this paper, professionalism is a multifaceted and complex concept that involves considerable interaction between physicians, patients, society, and regulatory bodies [4].…”
Section: Discussionsupporting
confidence: 91%
“…Medical Professionalism is a relatively recent concept that was coined some fifteen years ago [19]. It is a backbone of modern medical practice [20] and a determinant of medical institutions' competitiveness [21] with an established positive effect on clinical outcomes [8]. The findings of the current study illustrate high reported levels of professional behavior among the physicians surveyed.…”
Section: Discussionmentioning
confidence: 58%
“…Diabetes mellitus is on the rise in developing countries, Saudi Arabia inclusive. It is estimated that by 2030, the prevalence of diabetes among those aged 20–79 years may increase to 7.7% [ 2 ]. According to the World Health Organization, the East Mediterranean region ranks second in the global diabetes prevalence.…”
Section: Introductionmentioning
confidence: 99%